Alcohol use and implications for public health: Patterns of use in four communities - Girish N; Kavita R; Gururaj G; Benegal Vivek (Wolters Kluwer Medknow Publications, 2010)
Background: Alcohol is one of the leading causes of death and disability globally and in India. Information on quantum and pattern of consumption is crucial to formulate intervention programs. Objectives: To identify the extent and pattern of alcohol use in urban, rural, town and slum populations using a uniform methodology. Materials and Methods: Door-to-door survey was undertaken and simple random sampling methodology was adopted; households were the primary sampling unit. One respondent in each alcohol-user household was randomly chosen for detailed interview. Results: Overall, 13% of males and females consumed alcohol. Proportion of users was greater in town (15.7%) and among 26-45 years (67.4%). Whisky (49%) and arrack (35%) were the preferred types and the preferences differed between rural (arrack) and urban (beer) areas. Nearly half (45%) of rural population were very frequent users (consuming daily or every alternate-days) as against users in town (23%) or slum (20%). Two-thirds were long-term users and the proportions were greater in the rural and town areas. While, overall 17% of the users were heavy-users, frequent-heavy-drinking was more in slum and rural areas. Nearly two-thirds consumed alcohol in liquor-shops, restaurants, bars and pubs. Habituation and peer-pressure were the key reasons for alcohol use. Conclusions: The study documented alcohol use and patterns of use in four different communities particularly in transitional areas using similar methodology. Many of the patterns identified are detrimental to health both immediate and over the long period of time.